1997
DOI: 10.1161/01.hyp.30.6.1431
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular Sensory Nerve Ca 2+ Receptor and Ca 2+ -Induced Relaxation of Isolated Arteries

Abstract: The present study tested two hypotheses: (1) that a receptor for extracellular Ca2+ (Ca2+ receptor [CaR]) is located in the perivascular sensory nerve system and (2) that activation of this receptor by physiological concentrations of extracellular Ca2+ results in the release of vasodilator substance that mediates Ca2+-induced relaxation. Reverse transcription-polymerase chain reaction using primers derived from rat kidney CaR cDNA sequence showed that mRNA encoding a CaR is present in dorsal root ganglia but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
82
2
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(102 citation statements)
references
References 39 publications
16
82
2
2
Order By: Relevance
“…However, the recent discovery of the CaR in vascular tissues raises the possibility that such a receptor could play a role also in modulating contractility in response to changes in [Ca 2ϩ ] o . The CaR has been found in a wide range of rat small arteries: mesenteric, basilar, renal, coronary (10,43), and here in subcutaneous vessels, where we detected a 159-kDa CaR-reactive protein consistent with that observed in the rat kidney (47). Immunohistochemistry demonstrated that in mesenteric, basilar, renal, and coronary arteries, the receptor was localized to perivascular nerves (10,43), although the expression in coronary arteries was low compared with the other arteries.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…However, the recent discovery of the CaR in vascular tissues raises the possibility that such a receptor could play a role also in modulating contractility in response to changes in [Ca 2ϩ ] o . The CaR has been found in a wide range of rat small arteries: mesenteric, basilar, renal, coronary (10,43), and here in subcutaneous vessels, where we detected a 159-kDa CaR-reactive protein consistent with that observed in the rat kidney (47). Immunohistochemistry demonstrated that in mesenteric, basilar, renal, and coronary arteries, the receptor was localized to perivascular nerves (10,43), although the expression in coronary arteries was low compared with the other arteries.…”
Section: Discussionsupporting
confidence: 85%
“…The CaR has been found in a wide range of rat small arteries: mesenteric, basilar, renal, coronary (10,43), and here in subcutaneous vessels, where we detected a 159-kDa CaR-reactive protein consistent with that observed in the rat kidney (47). Immunohistochemistry demonstrated that in mesenteric, basilar, renal, and coronary arteries, the receptor was localized to perivascular nerves (10,43), although the expression in coronary arteries was low compared with the other arteries. Increasing [Ca 2ϩ ] o from 1.5 to 5 mM caused a concentration-dependent relaxation of these arteries except for the coronaries, which showed very little response (43), suggesting that Ca o 2ϩ was activating a neuronally mediated vasodilatory response possibly through the CaR.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…As calcium in its normal levels was reported to induce vascular relaxation of isolated arteries through activation of calcium receptors in the perivascular nerves 25 . The last proposed mechanism that explain the association between Ca and ICH is that lower serum Ca could reflect a poor liver function as stated by Inuo et ., 13 who observed in their study a higher percentage of ICH patients having poor liver function and hence poor coagulation resulting in the large hematoma volume.…”
Section: Discussion:-mentioning
confidence: 99%